A pint a day raises a man's pay; but smoking blows that gain away - Jan C. van Ours (Institute for the Study of Labor (IZA), 2002)
This paper studies the wage effects of the use of alcohol and tobacco. The analysis based on a recent survey in the Netherlands shows that for males the use of tobacco has a negative wage effect of about 10% while the use of alcohol has a positive wage effect of about the same size. The wages of females are not affected by smoking and drinking.
Keywords: D12; C41; I19; 330; drinking; smoking; wages; earnings regressions; Rauchen; Alkoholkonsum; Lohn; Geschlecht; Schätzung; Niederlande